POPULATION OF DOUBLE WHITE DWARFS IN THE GALACTIC CENTER - Panamarev, T.; Otebay, A.; Shukirgaliyev, B.; Kalambay, M.; Just, A.; Spurzem, R.; Berczik, P.; Omarov, Ch. (Academic Scientific Journal of Computer Science, 2020)
Upcoming space-born gravitational wave interferometers will monitor gravitational radiation at low frequency range. This will allow to study double white dwarf mergers and improve our understanding of physical processes involved. High stellar densities in galactic cores may imply enhanced binary compact object formation and coalescence compared to the galactic field. In this paper we analyze data from direct one-million-body simulation of the Milky Way Galactic center to describe properties of double white dwarf binaries and discuss their contribution to the gravitational radiation. We show that 7% of all white dwarf - white dwarf pairs are likely to undergo the gravitational wave driven merger resulting in a merger rate of . Therefore, we show that double white dwarf merger rate in the Galactic center is larger than that in the Galactic field. The obtained results may be used in future studies of white dwarf merger outcomes and their contribution to the gravitational radiation.